2018
DOI: 10.1101/243402
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of mannitol metabolism genes inSaccharinaexplains its key role in mannitol biosynthesis and evolutionary significance in Laminariales

Abstract: As a unique photosynthetic product in brown algae, mannitol exhibits high synthesis and accumulation in Saccharina japonica. Mannitol acts as a carbon-storage compound and is an osmoprotectant, imparting increased tolerance to osmotic stress. However, the underlying biochemical and molecular mechanisms in macroalgae have not been studied. Analysis of genomic and transcriptomic data has shown that mannitol metabolism in S. japonica is a circular pathway composed of four steps. In this study, one S. japonica man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…As indicated in Table 2, similar biochemical properties were observed when comparing kinetic constants of SjaM1Pase1 and SjaM1Pase2 on mannitol-1P. In S. japonica, it was suggested, based on gene expression analysis, that SjaM1Pase1 was the main M1Pase responsible for production of mannitol, whereas SjaM1Pase2 may support mannitol synthesis under changes in environmental conditions (Chi et al, 2018b). Interestingly, in Ectocarpus sp., the gene coding for EsM1Pase2 was not found to be differentially expressed under short-term abiotic stress conditions, while EsM1Pase1 was downregulated under oxidative and hyposaline conditions (Dittami et al, 2009).…”
Section: Biochemical Characterization Of Esm1pase1short Recombinant Psupporting
confidence: 61%
See 4 more Smart Citations
“…As indicated in Table 2, similar biochemical properties were observed when comparing kinetic constants of SjaM1Pase1 and SjaM1Pase2 on mannitol-1P. In S. japonica, it was suggested, based on gene expression analysis, that SjaM1Pase1 was the main M1Pase responsible for production of mannitol, whereas SjaM1Pase2 may support mannitol synthesis under changes in environmental conditions (Chi et al, 2018b). Interestingly, in Ectocarpus sp., the gene coding for EsM1Pase2 was not found to be differentially expressed under short-term abiotic stress conditions, while EsM1Pase1 was downregulated under oxidative and hyposaline conditions (Dittami et al, 2009).…”
Section: Biochemical Characterization Of Esm1pase1short Recombinant Psupporting
confidence: 61%
“…In contrast, in the brown alga S. japonica, significant phosphatase activity for both SjaM1Pases was also detected in presence of others substrates, such as glucose-1P, glucose-6P, and fructose-6P. Furthermore, the highest activity of SjaM1Pase2 was measured with glucose-1P (Table 1) (Chi et al, 2018b), as also observed for the M1Pase of the red alga Dixoniella grisea (Eggert et al, 2006). However, this latter result should be taken with caution because activities were measured on algal crude extracts, and not with (partially) purified proteins.…”
Section: Biochemical Characterization Of Esm1pase1short Recombinant Pmentioning
confidence: 94%
See 3 more Smart Citations